Expression analysis of E-cad and vascular endothelial growth factor in triple-negative breast cancer patients of different ethnic groups in western China. Issue 42 (October 2017) - Jiang, Weihua; Li, Yongtao; Ou, Jianghua; Wang, Xiaowen; Zhang, Chenguang; Yi, Lina; Xue, Laiti; Zhang, Mingshuai
Abstract : Abstract: The aim of this article is to investigate the expression of E-cadherin (E-cad) and vascular endothelial growth factor (VEGF) in triple-negative breast cancer (TNBC) of Han and Uygur women patients in western China, and their relationship with clinical features of TNBC. Totally, 172 cases of Han TNBC patients and 79 cases of Uighur TNBC patients were enrolled. The expressions of E-cad and VEGF were detected with immunohistochemistry. The correlation of E-cad and VEGF expression with lymph node metastasis, TNM stage, and histological grade were analyzed. The 5-year disease-free survival rate of the 2 groups was also evaluated. There was no significant difference in the 5-year disease-free survival rate ( P > .05) and the expression of E-cad between the 2 groups. The positive rate of VEGF in Han was significantly lower than that in Uygur ( P < .05). The expression of E-cad was negatively correlated with lymph node metastasis, TNM stage, and histological grade (−1⩽ r < 1, P < .05). However, the expression of VEGF was positively correlated with lymph node metastasis and TNM staging (0 < r < 1, P < 0.05), but not with histological grading. The expression of E-cad and VEGF and their relationship with clinical features of TNBC suggest that Uygur TNBC patients might have different prognostic factors as compared with Han patients.